2011
DOI: 10.1590/s1676-06032011000500027
|View full text |Cite
|
Sign up to set email alerts
|

Checklist de Siphonaptera (Insecta) do Estado de São Paulo

Abstract: Resumo: As pulgas são insetos hematófagos na fase adulta e que atuam como agentes infestantes ou como vetores de patógenos. Seus hospedeiros são animais endotérmicos, essencialmente mamíferos e, predominantemente roedores. A sifonapterofauna do Estado de São Paulo representa 61,3% (38/62) da brasileira, sendo a mais rica quando comparada com outros estados em número de espécies ou gêneros. Algumas espécies são conhecidas apenas por um dos sexos; outras, através de pequeno número de exemplares colecionados. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
12
0
6
Order By: Relevance
“…The Siphonaptera are small, wingless, holometabolous insects that parasitize endothermic animals, especially mammals (LINARDI, 2011). Ctenocephalides felis felis Bouché, 1835 (Pulicidae) is permanent parasite and the primary flea infesting cats and dogs in most of the world (DRYDEN & RUST, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The Siphonaptera are small, wingless, holometabolous insects that parasitize endothermic animals, especially mammals (LINARDI, 2011). Ctenocephalides felis felis Bouché, 1835 (Pulicidae) is permanent parasite and the primary flea infesting cats and dogs in most of the world (DRYDEN & RUST, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The higher incidence of P. irritans during colder times of the year (Figures 1-3) is noteworthy, as this species has a Neotropic origin (LEWIS, 1972). The Pulicidae may be changing its habits of seeking the host only for feeding (LINARDI, 2011), as the canine host also provides protection against abiotic conditions. In another study (SILVA et al, 2016), our research group, has shown the preference of P. irritans for long-haired dogs, confirming a trend for this flea to remain in the dogs, thus changing their eating behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Ctenocephalides felis Bouché 1835 is the most frequent species found in dogs and cats in Europe and in America (CASTRO;RAFAEL, 2006;STALLIVIERI et al, 2009), while Ctenocephalides canis Curtis 1826 seems to have a more restricted geographical distribution (MARCHIONDO et al, 2007), better adapting to low temperature regions (GUIMARÃES et al, 2011;OLIVEIRA;RIBEIRO, 1983). Pulex irritans Linnaeus 1758 is a cosmopolitan Pulicidae of eclectic food preferences whose adults usually do not reside on the body of the host only seeking the host for biting (LINARDI, 2011). There are reports from several countries showing that this flea parasitizes different species of domestic animals such as dogs and cats (DOBLER; PFEFFER; 2011), sheep, goats, cattle and pigs (DOMÍNGUEZ-PEÑAFIEL et al, 2011;KAAL et al, 2006;RAHBARI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The number of flea species in the Neotropics ( n = 289) is similar to those in the Nearctic and Afrotropics ( n = 299 and n = 275, respectively), but much smaller than that in the Palaearctic ( n = 892) (Medvedev & Krasnov, 2006). In Brazil, only 62 species and subspecies of fleas have been recorded (Linardi, 2011), although Brazil is considered to represent a hotspot of global biodiversity (Mittermeier et al , 1998; Myers et al , 2000) and occupies a vast area. Furthermore, flea fauna in Brazil and, in general, in the entire Neotropics is composed mainly of species that: (a) belong to species‐poor genera, and (b) have narrow geographic ranges (Medvedev, 2005).…”
Section: Discussionmentioning
confidence: 99%